The return of the loan : commercial mortgage investing after the 2008 financial crisis - Furfine, Craig; Fishbein, Mike ([London] : SAGE, 2016)
Zoe Greenwood, vice president at Foundation Investment Advisors, was glancing through the offering memorandum for a new commercial mortgage-backed securities (CMBS) deal on April 1, 2010, a time when the opportunities for commercial mortgage investors had been bleak to the point of comical. This new CMBS deal represented the first opportunity to buy CMBS backed by loans to multiple borrowers since credit markets had shut the securitization pipeline in June 2008. The offering gave Greenwood a new investment opportunity to suggest to her firm's latest client. She had planned to recommend an expansion in her client's traditional commercial mortgage business, but these new bonds looked intriguing. Could the new CMBS offer her client a superior risk-return tradeoff compared with making individual mortgage loans?
Originally Published in: Furfine, C., & Fishbein, M. (2013). The Return of the Loan: Commercial Mortgage Investing after the 2008 Financial Crisis (case revised 06/09/2013). 5-113-005. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Real property -- Economic aspects -- Case studies; Real property -- Finance -- Case studies